IMPORTANCE OF INNOVATION FACTORS IN SUSTAINABLE ECONOMIC DEVELOPMENT IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2023)
The article presents the introduction of ICT in the economy, the application of innovations and the optimization of the country's economy policy as one of the crucial factors for ensuring sustainable e conomic evolvement. It also considers the provision of sustainable economic growth as the foundation for increasing the competitiveness of the national economy.